2015
DOI: 10.1007/s11897-015-0259-3
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring of Self-Management Interventions in Patients With Heart Failure

Abstract: The effectiveness of heart failure (HF) self-management interventions varies within patients suggesting that one size does not fit all. It is expected that effectiveness can be optimized when interventions are tailored to individual patients. The aim of this review was to synthesize the literature on current use of tailoring in self-management interventions and patient characteristics associated with self-management capacity and success of interventions, as building blocks for tailoring. Within available trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 118 publications
(109 reference statements)
2
43
0
Order By: Relevance
“…Our findings are supported by multiple observational studies, reporting that both self-efficacy and activation have effects on SM(Bos-Touwen et al 2015a, Peters-Klimm et al 2013, Wolever et al 2011, Cooper et al 2011, Begum et al 2011). However, the positive effect of self-efficacy on SM shown in the observational study was not present in the intervention studies aimed to promote SM behavior through efficacy-enhancing interventions (van Dijk-de Vries et al 2015, Paradis et al 2010).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our findings are supported by multiple observational studies, reporting that both self-efficacy and activation have effects on SM(Bos-Touwen et al 2015a, Peters-Klimm et al 2013, Wolever et al 2011, Cooper et al 2011, Begum et al 2011). However, the positive effect of self-efficacy on SM shown in the observational study was not present in the intervention studies aimed to promote SM behavior through efficacy-enhancing interventions (van Dijk-de Vries et al 2015, Paradis et al 2010).…”
Section: Discussionsupporting
confidence: 87%
“…Non-experimental studies showed significant correlations between self-efficacy and SM in HF patients(van der Wal. 2010, Bos-Touwen et al 2015a, Peters-Klimm et al 2013, Schnell-Hoehn et al 2009). However, experimental studies failed to demonstrate that increased knowledge and self-efficacy led to increased SM behaviors in HF patients(Riegel.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically relevant potential effect modifiers (i.e., variables, such as sex or age, that modify the effect of self-management interventions) were selected based on the self-management literature in HF patients 19 and availability of comparable data across trials. The selected patient characteristics are presented along with the baseline data in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Supported by observational studies, 4,911 increased self-efficacy results in the improvement in SM behaviors. However, experimental studies have not demonstrated that increased knowledge and self-efficacy lead to increased SM behaviors in HF patients 1,7,12 …”
Section: Introductionmentioning
confidence: 99%